Analysing the Effect of Conflict on Nutrition Supply: Evidence from Conflict-affected South Asian Countries - Sithy Jesmy Abdul rasheed; Mohd Zaini Abd Karim; Shri Dewi Applanaidu (International Journal of Supply Chain Management, 2017)
Ensuring food security depends on sufficient intake of nutrition. However, malnutrition is a very serious problem and on-going concern in conflict-affected five countries in South Asia. International Food Policy Research Institute (IFPRI) and other international organizations accepted that conflict is a unique reason for malnutrition in conflict-affected developing world. The key objective of present research is to examine the effect of conflict on nutrition supply in conflict-affected five countries in South Asia, namely, Bangladesh, India, Nepal, Pakistan and Sri Lanka from 1980 to 2014 by employing the PSS-ARDL bounds test approach to cointegration. Empirical findings of this study provide an evidence that conflict is a single most important reason among included variables for poor nutrition intake (calorie intake) in South Asia. This finding is more useful to the policy-makers and the government, to take efficient steps to minimize and prevent conflict in order to achieve economic development through enhancing human development.